Layered ternary metal oxides: Performance degradation mechanisms as cathodes, and design strategies for high-performance batteries. (June 2020) - Liu, Lehao; Li, Meicheng; Chu, Lihua; Jiang, Bing; Lin, Ruoxu; Zhu, Xiaopei; Cao, Guozhong
Graphical abstract: Highlights: Ni-rich NCM/NCA materials have great application prospects in Li-ion batteries. The composition/structure/morphology instabilities cause the poor battery performance. Modifications on the NCM/NCA materials/electrode/electrolyte improve the performance. Future researches focus on hybrid coating, particle control, functional additive, etc. Abstract: Layered Li[Nix Coy Mz ]O2 (M = Mn or Al, so-called NCM/NCA) ternary cathode materials have attracted a lot of intensive research efforts for high-performance lithium-ion batteries, because of their combined advantages with respect to energy density, production cost and environmental friendliness. However, those ternary metal oxides (especially Ni-rich) suffer from a few electrochemical cycling problems, such as strong capacity fading, severe voltage decay and safety issues. These problems are attributable mainly to the instability/irreversibility of the chemical composition, crystal structure and particle morphology, and the consequent undesirable physical/chemical processes during the synthesis and lithiation/delithiation processes. To circumvent these obstacles, a variety of strategies based on materials, electrode and electrolyte designs are investigated to effectively stabilize the NCM/NCA cathodes and to improve the electrochemical and thermal performance. This review scrutinizes the performance degradation mechanisms of the NCM/NCA materials and summarizes the recent advances in the materials, electrode and electrolyte levels by focusing on the relationships between the composition, structure, morphology, and properties. This paper intends to provide an easy entry for a comprehensive, systematic and deep understanding of the fundamentals, and offer a critical analysis and summary what have been done in the field and what are the challenges or hurdles to overcome.